Evaluating the Usability and Engagement of a Gamified, Desktop, Virtual Art Appreciation Module - Sitong Li; Nurfaradilla Mohamad Nasri; Helmi Norman (Multimodal Technologies and Interaction)
Traditional art appreciation instruction relies heavily on textbooks, slides, or videos, limiting student engagement and immersion. To address this issue, this study proposes a desktop VR (GDVR) art appreciation module based on a gamification approach. Unlike traditional VR art learning environments, the GDVR module combines real-time feedback and gamification elements to increase students’ motivation and understanding of information. This study used focus group interviews to evaluate the usability of the GDVR module, as well as student engagement. In addition, on-screen observations have been adopted to capture student interaction behavior and navigation patterns, providing greater insight into usability. Forty Chinese middle school students participated, and the data were analyzed thematically. The results show that the GDVR module demonstrates stable technical performance, intuitive navigation, and a high level of immersion. Moreover, most students find it more engaging than traditional methods, noting that the real-time feedback system significantly enhanced their engagement with and understanding of the material. Furthermore, this study highlights the practical application potential of utilizing low-cost, desktop-based virtual reality systems in the context of middle school art appreciation. Finally, the study acknowledges its limitations and provides recommendations for future research to further refine and expand the application of GDVR in the field of art education.